Use of two additives for improving nutritional value of mixed silages of Cenchrus purpureus x C. glaucum (OM-22 hybrid) and Moringa oleifera - Rodríguez, R.; Ontivero, Yadiana; Gómez, Sarai; García, Yaneisy; Sosa, Dailyn (Cuban Journal of Agricultural Science, 2020)
The objective of the current study was to evaluate the effect of inclusion of sweet potato tubers (Ipomoea batatas) and Pediococus pentosaceus LB-25 on the nutritional value of mixed silages of Cenchrus purpureus x Cenchrus glaucum (OM-22 hybrid) and Moringa oleifera, by analyzing its chemical composition and indicators of its in vitro fermentation. A completely randomized experimental design with a factorial arrangement (3x2) was used, in which the main factors were the 3 levels of sweet potato inclusion (0, 25 and 50%) and the inclusion or not of Pediococcus. DM yield of the silage was decreased by 50% of tubers. Sweet potato inclusion level decreased pH, DM, NDF and ADF, while the inclusion of LB-25 only increased NDF from 61.5 to 64.5% (P <0.05). Neither of the two factors affected protein content of silages (P> 0.05). A tendency to increase potential and fractional rate of gas production was observed as sweet potato level increased, reaching the highest potential in the silage forage + 50 % sweet potato + LB-25 (662.69 mL g incOM-1). DAIVMS increased with 50% of sweet potato (P = 0.2101). It is concluded that the inclusion of sweet potato tubers in mixed silages of C. purpureus x C. glaucum (OM-22 hybrid) and M. oleifera improved the nutritional value of conserved materials, with the best results when 50 % was included. On the other hand, the use of P. pentosaceus LB-25 strain, at 5% (v/w), did not influence the nutritional quality of evaluated silages, except that NDF content increased. Key words: fermentation, in vitro technique, sweet potato tuber, Pediococcus pentosaceus LB-25